2004
DOI: 10.1103/physrevlett.92.025701
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Liquid Transition in the Molecular Liquid Triphenyl Phosphite

Abstract: We found both nucleation-growth-type and spinodal-decomposition-type transformation from one liquid state to another in a "molecular liquid," triphenyl phosphite (TPP). Binodal and spinodal temperatures of this transition at ambient pressure were determined by the characteristics of morphological evolution, domain-growth kinetics, and rheological evolution. Furthermore, a distinct thermal signature of the glass transition of a second liquid was also detected in addition to that of an ordinary liquid. These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
248
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(282 citation statements)
references
References 14 publications
33
248
1
Order By: Relevance
“…[10][11][12][13] There are some striking similarities between the slushy state of supercooled glycerol and the glacial state of TPP. For example, the rheological experiments on the glacial state of TPP shows that the maximum G′ is order of 10 6 Pa, 12 close to 10 7 Pa of the slushy phase of glycerol. Both moduli are far below their respective crystalline moduli.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] There are some striking similarities between the slushy state of supercooled glycerol and the glacial state of TPP. For example, the rheological experiments on the glacial state of TPP shows that the maximum G′ is order of 10 6 Pa, 12 close to 10 7 Pa of the slushy phase of glycerol. Both moduli are far below their respective crystalline moduli.…”
Section: Discussionmentioning
confidence: 99%
“…A first-order transition has been reported to occur in TPP at ambient pressure a few degrees Kelvin above T g (40)(41)(42). To our knowledge, a liquid-to-liquid transition occurring below the conventional T g has not been previously shown.…”
mentioning
confidence: 86%
“…Indeed, for the highly nonequilibrium path that we follow, it is not evident how the LDA-to-HDA transformation should proceed, i.e., whether it should exhibit spontaneous nucleation, as in equilibrium liquid-to-crystal first-order phase transitions, or if it should exhibit spinodal decomposition, with no distinct phase separation. Experiments performed by Tanaka and collaborators with triphenylphosphite (TPP) 76 and n-butanol, 77 as well as mixtures of glycerol and water 78 (where LDL and HDL have same composition), indicate the existence of a LLPT. In all these works, it was observed that, in some cases, the LLPT exhibited spontaneous nucleation, while in others, it showed spinodal decomposition.…”
Section: B Structure Of Lda and Hdamentioning
confidence: 99%